Labil Carbon as an Indicator of Soil Biological Activity in the Application of Microbial Inoculants and Soil Conditioner Containing Ca - Prettl, Nándor; Biró, Borbála; Nugroho, Priyo Adi; Juhos, Katalin (Journal of Central European Green Innovation, 2022)
Labil organic carbon (LOC) content, the active C=POXC, i.e the permanganate oxidizable C is a common method in general to evaluate the current soil microbial activity. LOC method is able to estimate the C-forms, available both the plants and the microbes in soils. LOC is the easily oxidizable forms of soil organic matter – like microbial biomass and carbohydrate C – which is a sensitive indicator of soil management in comparison with the known Total Organic Carbon (TOC) content. Pot and field experiments were designed on siltic Luvisol (pH=4.91; SOM=1.64 %; available P2O5=66 mg kg-1) and on silty clay Gleysol (pH=6.75; SOM=2.53 %; available P2O5=303 mg kg-1), with Zea mays test-plant. We suggest, that LOC can be an approriate indicator to show the differences between soil types and the resulted soil biological activities. In case if the pH is improved through CaO-addition, both soil biological activity and LOC can be enhanced. Industrial biofertilizer products, as microbial inoculants (i.e. Pseudomonas putida, Azotobacter chroococcum, Bacillus circulans, B. megaterium, Funneliformis-, Claroideoglomus- and Rhizophagus sp.) could enhance LOC content in both soil types in the pot experiments at controlled environmental condition. In field experiment, however LOC could show dynamic changes in time, correlated both with the soil moisture and the structural changes of soil physical – management – parameters.